THE TANSUQNĀMA-I ĪLKHĀNĪ AS A HISTORICAL SOURCE OF TRADITIONAL MEDICINE IN CENTRAL ASIA - Kairanbayeva, Н.Н.; Tuyakbayev, Ө.О. (Journal of Oriental Studies, 2025)
Tansuqnāma-i Īlkhānī is a medieval medical translation that serves as a significant source not only for understanding Eastern medicine but also for exploring the traditional medical practices of Turkic tribes in Central Asia during that period. The text contains descriptions of human anatomy and physiology, methods for diagnosing various diseases, and types of treatments. This article provides a brief overview of the historical and scientific importance of Tansuqnama-i Ilkhani, examines its content and structural features, and analyzes the process of medical knowledge and practice exchange in Central Asia. To achieve these objectives, textual-comparative, historical-source analysis, and systematization methods were applied. As a result, it was established that this work, translated by the renowned scholar Rashid al-Din al-Tabib, represents a valuable heritage that reflects the convergence of cultures and the synthesis of medieval medical traditions and paradigms. Since the historical and cultural significance of this work has not previously been analyzed in Kazakhstani scholarship, the findings of this study are expected to serve as a practical basis for future historical-medical and source-based research. Keywords: history of medicine, traditional medicine, medieval treatises, Tansuqnāma-i Īlkhānī.